Photography in the Spanish Protectorate. Photographic archives in Fernando Valderrama’s Legacy from the Islamic Library (AECID Library) - Olivera Zaldua, María (Revista General de Información y Documentación, 2014)
The study of Spanish photography during the Protectorate (1912-1956) is a subject of great interest for someone wishing to find out photographers’ contribution to the history and culture of Spanish North African territories. In that regard, current publications are allowing us to unveil many authors who had remained anonymous so far, and whose works are basic to recover and maintains historical memory. The photographic base of Fernando Valderrama’s Legacy, kept in the Islamic Library, which belongs to the Spanish Agency for International Cooperation for Development, is an essential source to complete any research, regarding both the contents and the photographers. The purpose of the present work is to analyse the base, to put it into context and to asses it in order to complete the research.